The effect of a single application of different fluoride varnishes on enamel subsurface lesions in vitro - ŞEN YAVUZ, BETÜL; YILMAZ, MÜESSER AHU; OKTAY, NİHAL ŞEHKAR; KARGÜL, BETÜL (My University, 2022)
This in vitro study aimed to evaluate the therapeutic effect of different fluoride ion (F) varnish formulations for controlling the carious development of enamel subsurface lesions and the F release into artificial saliva for 2 hr, 24 hr, 48 hr, and 7 days. Artificial enamel carious lesions were created and divided into 6 groups (5 varnish groups and a control group). Varnishes were applied to enamel specimens and then the specimens were incubated in artificial saliva, with the artificial saliva replenished daily. Varnish was removed and lesions were remineralized in artificial saliva for 24 hr. Surface microhardness was measured three times: (i) initially, (ii) after creating the artificial enamel lesions, and (iii) after applying the varnishes. The F release was analyzed after 2 hr, 24 hr, 48 hr, and 7 days of exposure using an ion-selective electrode. Data were analyzed using a One-way Analysis of Variance with the Tukey-Kramer Multiple Comparisons test and the Kruskal-Wallis test with the Dunns Multiple Comparisons test. The highest percentage surface microhardness recovery was found for the treatment with the MI Varnish. According to the percentage surface microhardness recovery results, a statistically significant difference was found between the varnishes and the control group (p < 0.05 and < 0.001). All varnishes released measurable levels of fluoride ions. However, the release of F was the highest in the MI Varnish group (p < 0.01). Duraphat, Enamel Pro Varnish, and MI Varnish released the most F into artificial saliva. Calcium phosphate-based F varnishes improve the capacity of the enamel surface re -hardening. CPP containing F varnish had the highest release of F as compared to the other F releasing varnishes. Further in vivo investigations are also required to prove the clinical applications of the different ingredients containing varnishes.
Keywords: Eczacılık; Meslek Bilimleri; Farmasötik Toksikoloji; Sosyal ve Beşeri Bilimler; Sosyoloji; Yaşam Bilimleri; Sağlık Bilimleri; Temel Bilimler; Pharmacology and Therapeutics; Professional Sciences; Pharmaceutical Toxicology; Social Sciences and Humanities; Sociology; Life Sciences; Health Sciences; Natural Sciences; KAMU, ÇEVRE VE İŞ SAĞLIĞI; Sosyal Bilimler Genel; Sosyal Bilimler (SOC); TOKSİKOLOJİ; Farmakoloji ve Toksikoloji; Yaşam Bilimleri (LIFE); PUBLIC, ENVIRONMENTAL & OCCUPATIONAL HEALTH; SOCIAL SCIENCES, GENERAL; Social Sciences (SOC); TOXICOLOGY; PHARMACOLOGY & TOXICOLOGY; Life Sciences (LIFE); İş Sağlığı ve Terapisi; Güvenlik Araştırması; Sağlık (sosyal bilimler); Genel Sosyal Bilimler; Toksikoloji; Farmakoloji, Toksikoloji ve Eczacılık (çeşitli); Halk, Çevre ve İş Sağlığı; Epidemiyoloji; Sağlık, Toksikoloji ve Mutajenez; Fizik Bilimleri; Sosyal Bilimler ve Beşeri Bilimler; Occupational Therapy; Safety Research; Health (social science); General Social Sciences; Toxicology; Pharmacology, Toxicology and Pharmaceutics (miscellaneous); Public Health, Environmental and Occupational Health; Epidemiology; Health, Toxicology and Mutagenesis; Physical Sciences; Social Sciences & Humanities; CPP-ACP; Demineralization; Fluoride release; Fluoride varnishes; Microhardness; Remineralization; Tricalcium phosphate